A content analysis of the language quality of thematic textbooks for elementary school students - Tina Mardiyana; Endang Fauziati; Yeny Prastiwi; Minsih Minsih (Journal of Education and Learning (EduLearn), 2023)
Primary school students rely heavily on textbooks for instruction. Using thevariety of textbooks, a description of the theme textbooks’ linguistic qualityis conspicuously absent, particularly for students in the fifth grade. Languagefit for students’ growth, communicative language, and coherence andcohesiveness were all included in this study’s analysis of textbooks’language quality. Qualitative content analysis was used in this study'smethodology. All texts from the heat and transfer-themed of fifth-gradetextbooks published by the Indonesian Ministry of Education and Culture,Yudhistira, and Erlangga publishers were included in the study.Documentation was utilized to collect the data. Sample, record, reduce,infer, and narrate were all data analysis approaches used. The findings of thisresearch indicated that the three publishers’ textbooks had excellentlanguage quality in terms of language compatibility for students’ growth andthe communicative language issued by the Indonesian Ministry of Educationand Culture and Erlangga was wonderful, but Yudhistira was awful. Therewere a lot of solid points made in the Ministry of Education and Culture’spublications. Both Yudhistira and Erlangga performed admirably. Thequality of textbook language was found to be satisfactory in this study.